STRESS LEVELS AND SLEEP QUALITY OF NURSES AT GOTONG ROYONG SURABAYA HOSPITAL - Theresia Cindy Limantoro; Handi Suyono; JF Tri Arimanto Y (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Stress is a condition that requires individuals to react physically, psychologically, and behaviorally to a change. Sleep quality is a measure of how well a person sleeps. Increased stress and poor sleep quality can affect nurses' health conditions (physical, psychological, behavioral) and work performance.Objective: To determine the correlation between stress levels and the sleep quality of nurses at Gotong Royong Hospital Surabaya.Methods: Cross-sectional method was carried out with a purposive sampling technique. Data collection was done online using Jotform. The stress level questionnaire used was the Perceived Stress Scale (PSS) and sleep quality with the Pittsburgh Sleep Quality Index (PSQI). PSS results consist of mild, moderate, and severe stress, while PSQI results are good and bad sleep quality.Results: 72 people (92.3%) experienced moderate stress, and 64 (82.1%) had poor sleep quality. From the Spearmancorrelation test results, a significance value of 0.069 (p>0.05) was obtained, which means it was not significant.Conclusion: There is no correlation between stress levels and the sleep quality of nurses at Gotong Royong Hospital Surabaya.